A government approach to address coal overcapacity in China. (1st January 2021) - Dong, Changgui; Qi, Ye; Nemet, Gregory
Abstract: Coal production in China has direct implications for globally important issues such as sustainable development, climate change, and energy transition. However, coal is prone to recurring, and sometimes extended, periods of overcapacity where production capacity is significantly and persistently larger than actual production or demand. Mainstream economics holds that price signals will clear these markets so that extant overcapacity would exit automatically. However, such a self-clearing process usually takes long time and is full of exiting barriers. In this article, we innovatively use a cobweb model to compare China's government actions to an optimal strategy that minimizes the cost of cutting capacity, allowing us to evaluate the policies' effectiveness, speed, and cost efficiency. We find that China's efforts at curbing coal overcapacity have been effective, timely, and only modestly costly in returning the coal market to a sustainable equilibrium. The strong "visible hand" of China's government has been an effective mechanism of governance to coordinate collective actions of market participants and avoid the overcapacity trap. By removing 500–800 million tons of coal production capacity permanently, China has decarbonized its energy supply system within a relative short time period, thus making more room for the development of renewable energy. Highlights: Policy measures to address coal overcapacity are evaluated for China. Cobweb model and optimization method are utilized for the task. The government approach is effective, speedy and cost efficient. The "visible hand" may be more advantageous in addressing overcapacity. Removing coal capacity from the market has substantial carbon benefits.